Studi Kasus Konsumsi Suplemen pada Member Fitness Center di Kota Yogyakarta - Hidayah, Taufiq; -, Sugiarto (Media Ilmu Keolahragaan Indonesia, 2013)
The purpose of this study to find out how the members of supplements on the fitness center in the city of Yogyakarta. Type a descriptive qualitative research study, the technique of the test through a questionnaire survey. Total sample of 30 people with accidental sampling technique. The results showed that: 1) the characteristics of the majority of member fitness aged 20-29 years (73.7%), is still active as a student (56.7%), and by 6.7% as a housewife. 2) respondents have a grasp on the definition of supplements (86.6%), which is derived from advertising, print media, electronic media (63.3%) in the form of amino, high milk protein and creatine (66.6%). 3) the majority of respondents use tablets (70%), obtained from the purchase (96.7%), consumed 1-3 times / day (always) of (83.3%) to increase the muscle mass of (59.9%). 4) the majority of respondents (73.3%) increased his stamina and health after taking the supplement. Conclusions: 1) should be someone over the age of 30 years and mother housewife improve motion activity, 2) the principles of exercise should be increased in line with the benefits of supplements for stamina and health.